2009
DOI: 10.1213/ane.0b013e31819cb1f3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Versus Landmark-Based Technique for Ilioinguinal-Iliohypogastric Nerve Blockade in Children: The Implications on Plasma Levels of Ropivacaine

Abstract: The pharmacokinetic data indicate faster absorption and higher maximal plasma concentration of LA when ultrasound was used as a guidance technique for INB compared with the landmark-based technique. Thus, a reduction of the volume of LA should be considered when using an ultrasound-guided technique for INB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 11 publications
1
62
1
4
Order By: Relevance
“…Microdialysis probes were removed at the end of the experiment. Quantitative ropivacaine assay Ropivacaine concentrations in venous plasma were determined by high-performance liquid chromatography (HPLC) with ultraviolet detection using essentially the procedures as those reported earlier [14]. Briefly, 100 μl of plasma was mixed with 50 μl of chlorzoxazone in water (internal standard) and extracted with 50 μl 1 M Na 2 Co 3 plus tertiary butylmethylether.…”
Section: Study Daymentioning
confidence: 99%
“…Microdialysis probes were removed at the end of the experiment. Quantitative ropivacaine assay Ropivacaine concentrations in venous plasma were determined by high-performance liquid chromatography (HPLC) with ultraviolet detection using essentially the procedures as those reported earlier [14]. Briefly, 100 μl of plasma was mixed with 50 μl of chlorzoxazone in water (internal standard) and extracted with 50 μl 1 M Na 2 Co 3 plus tertiary butylmethylether.…”
Section: Study Daymentioning
confidence: 99%
“…The authors also believe using lower volumes could reduce the risk of local anesthetic toxicity . The use of lower volumes of local anesthetic is also supported by a recent pharmacokinetic study that found higher plasma levels of ropivacaine using ultrasound guidance when compared to a single pop technique (Weintraud et al, 2009). …”
Section: Outcome and Discussionmentioning
confidence: 92%
“…In all these studies, the authors used single "pop" sensation techniques, injecting local anesthetics under external oblique muscle aponeurosis, with failure rates ranging from 25.8% to 33% [31,1,2,28,30]. In Kundra's study, injection of the local anesthetics above and below internal oblique muscle aponeurosis demonstrate a success rate of 94% [29].…”
Section: Discussionmentioning
confidence: 99%